Essential oil of lavender in anxiety disorders: Ready for prime time? - Malcolm, Benjamin J. (Ment Health Clin, 2018)
Anxiety disorders are some of the most common psychiatric disorders, with potentially debilitating consequences on individual function. Existing pharmacotherapies for anxiety disorders are limited by delay to therapeutic effect, dependence, tolerance, withdrawal, and abuse potential. Therefore, safe and evidence-based complementary or alternative therapies may be important allies in the care of patients with anxiety disorders. Essential oils are lipophilic and concentrated botanical extracts that exhibit many properties of drugs, although they are not Food and Drug Administration approved and have limitations characteristic of herbal preparations. Lavender essential oil has an extensive anecdotal history of anxiolytic benefit that has recently been supported by clinical efficacy studies. The 2 primary terpenoid constituents of lavender essential oil, linalool and linalyl acetate, may produce an anxiolytic effect in combination via inhibition of voltage-gated calcium channels, reduction of 5HT1(A) receptor activity, and increased parasympathetic tone. The objectives of this article are to provide a brief overview of lavender oil in aromatherapy, explore variability in the constituents of lavender oil, summarize its pharmacology and safety profile, as well as describe its body of research that has been conducted for anxiety.